Buddenbrooks - Mann, Thomas 1875-1955; Ströer, Hans P. 1956- (Warner Home Video, 2009)
The story of the decline and fall of a once-prestigious German family. Anxious to preserve their rapidly diminishing wealth, the Buddenbrook clan undergoes several marriages of convenience--which serve only to weaken the strain, until, as the 20th Century dawns, only two members of the family are left
Aspect ratio 2.35:1 (16:9)
Orig.: Bundesrepublik Deutschland 2008
Making of (14 Min.) ; Bericht über die Weltpremiere in Essen
Keywords: Buddenbrooks -- Film -- 2008; Families -- Drama; DVD-Video; Feature films; Film adaptations